Exploring the impact of a mental skills training curriculum with elite university student-athletes: A qualitative case study - Rose, S.; Burton, D. (Journal of Physical Education and Sport, 2024)
University courses for mental skills training (MST) and performance enhancement have been developed by sport psychology faculty and professionals to provide training for university student-athletes (Curry & Maniar, 2004). The integration of MST into both academic and sport settings can support the development of mental resilience, psychological well-being, and athletic performance in student-athletes, making it highly relevant for physical education programs. These interventions have also shown potential to enhance academic performance and coping skills while reducing anxiety. However, literature supporting the psychological and performance benefits of classroom-based MST courses remains limited, particularly in comparison to traditional sport training environments. This qualitative case study explored the effectiveness and experiences of a 16-week university MST course offered through a Movement Sciences department and designed specifically for elite student-athletes. Six participants across various sports engaged in semi-structured interviews conducted during the semester to assess their perceptions, challenges, and applications of MST both in and out of the classroom. Using transcription and thematic coding, 560 meaning units were identified and categorized into subthemes, themes, and two major dimensions: learning and high-performance mindset. The learning dimension encompassed themes such as applying MST, overcoming barriers, and a desire for self-improvement, while the high-performance mindset focused on student-athletes` expectations, perceptions, and limitations related to their sport. This study highlights the potential of classroom-based MST courses to enhance performance and psychological skills in student-athletes both in the classroom and in their sport. Findings provide practical recommendations for integrating MST into physical education curricula, emphasizing its role in fostering resilience and holistic development in both academic and athletic domains.